TOWARDS SUSTAINABLE MILK PRODUCTION IN EGYPT: AN ANALYTICAL POLICY FRAMEWORK - Rania Youssif; Fatma Mabrouk; Ahmed A. Mashaal; Alshaima M. Fangary; Moataz Eliw (Journal of Animal and Plant Sciences, 2026)
The current research provides an exhaustive analysis on the tendencies in the Egyptian dairy industry in relation to the efficacy of conflicts, future directions, and strategies for an improved efficiency in the dairy food security in the Egyptian dairy sector. Within this context, using economic models between 2005 and 2023, it was evident that there was a tremendous rise in the cow milk industry in terms of an average annual increase of 47.1 thousand tons at an annual compounded rate of 1.4%, while there was a tremendous drop in the buffalo milk industry as well as the goat milk industry with an annual rate of 3.7% and 6.6%, respectively. Therefore, even though there was a drop in the wheat-green fodder area under cultivation from 2.58 million acres to 1.75 million acres, the growth in the efficiency level of dry and concentrated feed with 40% and 43% improvement in efficiency, respectively, assisted in raising the productivity level due to the effective implementation of modern management practices, feed management, & technology implementation in the industry. The total milk production increased from 5.55 million tons to 7.37 million tons. The correlation study proved the existence of a positive relation between total dairy production and measures of quality of feed, hence establishing the effectiveness of optimal input management. The partial genetic substitute approach with a 25% replacement of local genetic strains of cows and buffaloes with superior foreign breeds projected an expected increase in total dairy production of 86%, thus meeting and exceeding the local needs of milk production for possible exports.
Keywords: Dairy production; Food Security; Self-sufficiency; Breed Improvement; Agricultural Policy; Egypt